Perbandingan Performa Web Services Yang Dibangun Menggunakan Arsitektur Monolithic dan Microservices pada Sistem Point of Sales - Fiqri Syah Redha (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
There have been many emerging approaches to software development in terms of architecture lately. One of them is the microservices architecture. The microservices architecture is often compared to the classic monolithic software architecture. Many organizations are starting to implement microservices architectures. However, deciding to implement a microservices architecture into software development is not easy. Many considerations must be taken into account when choosing a software architecture. In this study, the two architectures, namely monolithic and microservices, were compared to the development of the NekoToko POS system. The web services of the system were developed using these two architectures and tested for their performance through load testing. Tests were carried out with three different scenarios; monolithic uses Linux hosts, monolithic uses Docker, and microservices uses Docker. Parameters observed are CPU usage, memory usage, response time, and throughput. From the results of load testing using Locust with 100 users, the response time and throughput of the monolithic architecture are 421 milliseconds and 230.5 rps. While in the microservices architecture, the response time and throughput are 415 milliseconds and 233.8 rps. CPU and memory usage in microservices architecture (scenario 3) is on average 22% and 1,135 MB is greater than CPU usage in monolithic architecture (scenario 1). Therefore, the monolithic architecture was chosen for the NekoToko POS system because with smaller resources it can provide the same performance as microservices that use larger resources.